A change in management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Managing for Change: Leadership, Strategy and Management in Asian NGOs By I Smillie and J Hailey, Earthscan & Aga Khan Foundation Canada, 2001. 193 pp. ISBN 1853837229 GBP 16.95 Euro 27.40